Armageddon: Political Elites and Their Visions of a General European War before 1914. (November 2019) - Mulligan, William
Expectations of a general European war before 1914 remain a contentious area of historiographical debate. This article discusses how one particular group, political and diplomatic elites, imagined a future war before 1914. In contrast to the 'short-war myth', this article argues that political elites understood that war would bring in its wake revolution, chaos, and impoverishment. This article analyses the varieties of understandings of catastrophe among European political elites before 1914, the sources of their knowledge about the consequences of war, and the implications these visions of catastrophic warfare had for the conduct of international politics.